An advanced nurse-led clinic for patients following percutaneous coronary intervention. (2nd October 2020) - Ingram, Shirley; Quirke, Mary B; Loo, Bryan
Abstract : Percutaneous coronary intervention (PCI) is internationally recognised as the preferred initial treatment for acute coronary syndrome and as a treatment option for chronic coronary heart disease. The use of PCI has led to shorter inpatient stays. However, reduced length of stay can mean less opportunity for patient education. Once discharged from hospital, timely outpatient review encompassing symptom reassessment, advanced physical assessment, medication and cardiovascular risk management is a key component of patient care. In an Irish acute hospital setting, cardiology clinical nurse specialists and advanced nurse practitioners have established an advanced nurse-led post-PCI clinic. This article describes the post-PCI clinic and provides an overview of the patient profile and outcomes over a 2-year period, with an emphasis on advanced nursing roles and patient symptoms.